New Therapeutics Options for Pediatric Neuromuscular Disorders - Flotats-Bastardas, Marina; Hahn, Andreas (Frontiers in Pediatrics, 2020)
Neuromuscular disorders (NMDs) of Childhood onset are a genetically heterogeneous group of diseases affecting the anterior horn cell, the peripheral nerve, the neuromuscular junction, or the muscle. For many decades, treatment of NMDs has been exclusively symptomatic. But this has changed fundamentally in recent years due to the development of new drugs attempting either to ameliorate secondary pathophysiologic consequences or to modify the underlying genetic defect itself. While the effects on the course of disease are still modest in some NMDs (e.g. Duchenne Muscular Dystrophy), new therapies have substantially prolonged life expectancy and improved motor function in others (e.g. Spinal Muscular Atrophy and Infantile Onset Pompe Disease). This review summarizes recently approved medicaments and provides an outlook for new therapies that are on the horizon in this field.